Analisis Kesesuaian Beban Kerja Petugas Pendaftaran Rawat Jalan Dalam Peningkatan Mutu Pelayanan di RS Bhayangkara TK II Sartika Asih Bandung - Sabni Mauldy; Neni Rohaeni (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the suitability of outpatient registration officers’ workload in improving service quality at RS Bhayangkara TK II Sartika Asih Bandung. Registration services play a vital role as the front line of healthcare delivery, directly impacting overall patient satisfaction and service performance. High workloads without appropriate staffing levels can lead to inefficiency and a decline in service quality, particularly in terms of waiting times, accuracy of medical record data entry, and patient interaction. Materials and methods. This study employed a quantitative research design using observation and structured interviews. Data were collected from four registration officers and patient visit records throughout 2024. The workload was calculated using the Health Workload Analysis (ABK-Kes) method, taking into account available working hours, volume of tasks, and average time to complete each registration activity. Additional qualitative data were collected through interviews regarding SOP adherence and administrative responsibilities. Results. The findings showed that while registration services generally met quality indicators such as timeliness and communication, the current number of registration officers was insufficient. Based on ABK-Kes calculations, the ideal number of officers should be 10 to adequately handle the volume of outpatient visits. The study also revealed that officers perform not only registration but also multiple administrative tasks, contributing to a higher workload. Conclusions. To maintain service quality and reduce the risk of errors, adjustments to staffing based on workload analysis are necessary. It is recommended that the hospital implement strategic workforce planning, utilize integrated health information systems (SIMRS), and provide ongoing staff training to support efficient service delivery.